THE ORGANIZATION OF EDUCATION SYSTEMS IN MERCOSUR COUNTRIES - Souza, Kellcia Rezende; Miceli Kerbauy, Maria Teresa [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2019)
The article seeks to analyze the regulation of the organization of education systems in the Mercosur countries (Argentina, Brazil, Paraguay, Uruguay and Venezuela) and their relationship with the right to education. Based on the methodology of the comparative study, a bibliographic and documentary research with a qualitative approach was carried out. The documentary source was constituted in the current Constitutions of the countries that make up the mentioned block and the educational Legislation (Law of Guidelines and Bases and / or equivalent legislation). The results indicate that Brazil has a broader constitutional framework regarding the educational organization. Argentina, Paraguay, Uruguay and Venezuela demand infra-constitutional legislation to regulate the structuring of education. However, even with the strongest legal protection in its Magna Carta, Brazil lacks a legal framework that regulates its National Education System, unlike the other Mercosur countries, which instituted this structuring in their respective educational legislations.
Keywords: Mercosur; Educational policies; Teaching systems